Analysis of factors affecting the level of corruption: a study of ASEAN countries - Suhardi, Rapon Yuniar; Rahman, Arief (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2024)
This study aims to examine the influence of information systems, human resource quality, and economic capability on corruption levels in 10 ASEAN countries from 2010 to 2020. This study uses secondary panel data regarding the E-Government Development Index (HDI), Human Development Index (HDI), GDP per capita (PPP), and Corruption Perception Index (CPI). The data were analyzed using panel data regression with a Fixed Effects Model (FEM), selected based on the results of the Hausman test. The findings indicate that human resource quality has a significant negative effect on corruption levels. Meanwhile, information systems have a significant effect, indicating that technological progress contributes to reducing corruption, although its effectiveness may depend on institutional factors. On the other hand, economic capability does not show a significant effect on corruption. These results suggest that improving human resources is a crucial strategy in eradicating corruption in ASEAN countries, while technology and economic growth alone may not be sufficient without strong institutional support.